Cellulolytic bacteria isolation, screening and optimization of enzyme production from vermicompost of paper cup waste. (October 2020) - Karthika, A.; Seenivasagan, R.; Kasimani, R.; Babalola, O.O.; Vasanthy, M.
Highlights: Paper cup with polyethylene coating remains undegraded in environment. Cellulolytic enzyme activity was studied both qualitatively and quantitatively. Potential cellulolytic bacteria help in decreasing the duration of degradation. Paper cup waste degradation is substantiate by insilco analysis. Abstract: In the current scenario, used paper cups are disposed of without any proper treatment, thereby damaging the environment. Hence, the vermicomposting technique is preferred for managing these wastes. The ability of bacterial strains on cellulase enzyme (Endoglucanase, exoglucanase and β-glucosidase) production at altered pH and temperatures were focused in this study. Among nine bacterial strains Acinetobacter baumannii was found to have high enzyme activity. HPLC analysis confirms that about 45% of cellulose degradation occurred due to the action of bacterial consortia at 37 °C with pH 7. The overall period required for degradation takes only three months with the help of bacterial consortia while comparing to our previous study, which takes six months. The insilico study on three cellulose-degrading enzymes sequence were retrieved from NCBI, and analysed for multiple sequence alignment and phylogenetic tree construction. From the analysis, the endoglucanase SVK46152 ( Acinetobacter baumannii ) sequence got docked with cellopentaose with a high score value −11.07. Thereby we confirm that organism Acinetobacter baumannii was effective in paper cup degradation.